General correspondence materials, Harry Hoijer Collection - Hoijer, Dorothy; Hoijer, Harry, 1904-1976; Sapir, Edward, 1884-1939 (1935)
Two letters in the "Series I: Correspondence" section. A letter from Edward Sapir to Harry Hoijer, dated November 2, 1935, includes comparative data on verb forms in Dakelh ("Carrier"), Hupa, Tsetsaut, with some info on Tsuut'ina ("Sarsi"). A second letter, from Dorothy Hoijer to Whitfield Bell, includes brief identifying information on Harry Hoijer's Galice, Chiricahua, Mescalero, and Jicarilla consultants, plus a note on "Navaho Texts."